2007
DOI: 10.1103/physrevb.76.195421
|View full text |Cite
|
Sign up to set email alerts
|

Transport in chemically doped graphene in the presence of adsorbed molecules

Abstract: Motivated by a recent experiment reporting on the possible application of graphene as sensors, we calculate transport properties of 2D graphene monolayers in the presence of adsorbed molecules. We find that the adsorbed molecules, acting as compensators that partially neutralize the random charged impurity centers in the substrate, enhance the graphene mobility without much change in the carrier density. We predict that subsequent field-effect measurements should preserve this higher mobility for both electron… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
114
0
5

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 173 publications
(121 citation statements)
references
References 19 publications
2
114
0
5
Order By: Relevance
“…It is interesting to note that hole conduction is favored over electron conduction as negative back-gate fields result in higher drain current modulation compared to positive backgate fields. This is attributed to unintentional chemical doping by adsorbants during processing and handling of the sample [13], which is also believed to shift the current minimum towards positive E bg . After the deposition of the SiO 2 topgate dielectric, the IV transfer characteristics maintain their basic signature, but the current level and the current modulation are decreased dramatically, represented by hollow circles in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…It is interesting to note that hole conduction is favored over electron conduction as negative back-gate fields result in higher drain current modulation compared to positive backgate fields. This is attributed to unintentional chemical doping by adsorbants during processing and handling of the sample [13], which is also believed to shift the current minimum towards positive E bg . After the deposition of the SiO 2 topgate dielectric, the IV transfer characteristics maintain their basic signature, but the current level and the current modulation are decreased dramatically, represented by hollow circles in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Carrier scattering in supported graphene is attributed to a variety of sources including ripples in the graphene layer, point defects and their associated short-range potentials, electron-electron (hole-hole) interactions, charged impurities residing in the supporting substrate, and adsorbed atoms on the surface [5,6,7]. Earlier studies suggested that charged impurity scattering could explain the dominant behavior in experimental findings [5,8].…”
mentioning
confidence: 99%
“…1 On the other hand, certain graphene based device applications, such as graphene-based field-effect transistors (FETs) 2 or integrated circuits for nanoelectronics, 3,4 may require well-defined conducting properties of graphene in order to show stable performance. [5][6][7] Fortunately, the conspicuous response of graphene to contact with foreign active species can be turned into a beneficial control of the electronic structure of graphene. Adsorption of active molecular or atomic species on graphene is known to result in charge transfer to or from graphene, so-called surface transfer doping (STD).…”
mentioning
confidence: 99%